A lithium iron manganese phosphate positive electrode material, a preparation method and application thereof
Patent Information
- Application Number
- CN202610857224.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-06-15
AI Technical Summary
Existing technologies struggle to suppress manganese leaching from lithium iron manganese phosphate cathode materials while retaining the advantages of high voltage and high kinetics, leading to rapid capacity decay and reduced cycle life.
By utilizing the thermal decomposition temperature difference between manganese and iron sources during the preparation of lithium manganese iron phosphate cathode material, a partitioned configuration with low manganese and high iron in the outer region and high manganese in the inner region is constructed in the temperature field of spray-dried droplets. Furthermore, a first metal ion with an ionic radius smaller than that of manganese ions is incorporated to broaden the ion diffusion channels and reduce the migration barrier.
It significantly improves the room temperature and high temperature cycling performance of lithium manganese iron phosphate cathode materials, maintains a high voltage platform and high energy density, extends battery cycle life, and improves lithium-ion conduction rate and rate performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the technical field of batteries, and in particular to a lithium manganese iron phosphate cathode material, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries, as the core carrier of new energy storage and power batteries, require a synergistic improvement in the energy density, cycle stability, and safety of cathode materials. Olivine-type lithium iron manganese phosphate (LiMn) x Fe 1-x By partially replacing iron with manganese, lithium iron phosphate (LFP) can improve the operating voltage and energy density by 10-20% compared to conventional LFP, while retaining the advantages of high safety, long life and low cost. It has significant industrialization value in the field of power and energy storage batteries.
[0003] However, lithium iron manganese phosphate cathode materials suffer from intrinsic defects such as transition metal dissolution during cycling and storage, which has become a key bottleneck restricting their large-scale application. Conventional high-manganese systems (such as LiMn) 0.6 Fe 0.4 In PO4, manganese tends to accumulate on the particle surface, and Mn is generated during charging. 2+ Oxidized to Mn 3+ This triggers Jahn-Teller distortion, accompanied by disproportionation reactions to generate soluble Mn. 2+ Furthermore, under the corrosive effect of the acidic components in the electrolyte, surface manganese continues to dissolve, and the dissolved Mn... 2+ Migrating to the negative electrode deposition will damage the solid electrolyte interphase (SEI) film, thereby consuming active lithium and increasing interfacial impedance, ultimately leading to rapid capacity decay and a significant decrease in cycle life.
[0004] Existing modification methods mostly employ bulk homogenization, surface coating, and single-element doping. While bulk homogenization can reduce manganese content and alleviate dissolution, it sacrifices the energy density and core ion transport capacity of lithium iron manganese phosphate cathode materials. Surface coating only uses physical isolation such as metal oxides to suppress manganese dissolution, but the coating layer is prone to failure during cycling due to volume expansion or electrolyte erosion, and it cannot fundamentally optimize the difference in manganese content between the material surface and the core. Single-element doping also fails to distinguish between the surface dissolution prevention and the high kinetic requirements of the core, making it difficult to achieve synergy between structure and performance.
[0005] In summary, current technologies struggle to simultaneously suppress manganese leaching while retaining the high voltage and kinetic advantages of high-manganese cathode systems. Therefore, how to suppress surface manganese leaching and stabilize the lattice interface from a structural perspective, while maintaining high-rate transport characteristics in the core, has become a pressing issue in the research of lithium iron manganese phosphate cathode materials. Summary of the Invention
[0006] This invention provides a method for preparing lithium iron phosphate cathode material, which can inhibit the dissolution of surface manganese from the structural source and stabilize the lattice interface of the cathode material, thereby preparing lithium iron phosphate cathode material with both high rate transport characteristics and high cycle stability.
[0007] This invention provides a lithium manganese iron phosphate cathode material that maintains the high-rate transmission characteristics of high-manganese cathode materials while improving the lattice integrity and chemical stability of high-manganese cathode materials during long-cycle processes. This effectively avoids the problem of rapid battery capacity decay caused by the loss of active lithium due to manganese dissolution, thereby significantly improving cycle life.
[0008] This invention provides a positive electrode sheet that can better meet the requirements for battery rate performance and cycle life.
[0009] This invention provides a secondary battery that can improve the rate performance and cycle life of the battery.
[0010] In a first aspect, embodiments of this application provide a method for preparing a lithium manganese iron phosphate cathode material, comprising the following steps:
[0011] A mixture of raw materials including phosphorus source, manganese source, iron source, and lithium source, and a first dopant are ground and mixed, and then subjected to a first spray drying to obtain a first precursor powder; the decomposition temperature of the manganese source is 150-220℃; the decomposition temperature of the iron source is 240-300℃; the inlet air temperature of the first spray drying is 260-300℃, and the outlet air temperature is 80-150℃; the first dopant includes a first metal ion, and the ionic radius of the first metal ion is less than or equal to the ionic radius of the manganese ion.
[0012] The first precursor powder was sintered for the first time in a protective atmosphere to obtain lithium manganese iron phosphate cathode material.
[0013] In one possible implementation, after the first sintering is completed, the following steps are further included:
[0014] A second dopant is incorporated into the product of the first sintering, followed by a second spray drying to obtain a second precursor powder; the second dopant includes a second metal ion, the ionic radius of which is greater than that of the manganese ion.
[0015] The second precursor powder is then sintered a second time in a protective atmosphere to obtain lithium manganese iron phosphate cathode material.
[0016] In one possible implementation, the protective atmosphere is at least one of argon, helium, or nitrogen; and / or,
[0017] The initial spray drying rate is 5-50 mL / min; and / or,
[0018] The sintering temperature for the first sintering is 400-800℃, and the sintering time is 1-24h.
[0019] In one possible implementation, the inlet air temperature of the second spray drying is 200-400°C, and the outlet air temperature is 80-150°C; and / or,
[0020] The infeed rate for the second spray drying is 5-50 mL / min; and / or,
[0021] The second sintering temperature is 400-800℃, and the sintering time is 1-24h.
[0022] In one possible implementation, the first metal ion includes Mg. 2+ Zn 2+ Ti 4+ V 3+ Mo 6+ W 6+ At least one of them; and / or,
[0023] The second metal ion includes Zr 4+ 、Nb 5+ Ca 2+ Y 3+ Ce 3+ At least one of them.
[0024] In one possible implementation, the doping amount of the first metal ion is 500ppm-5000ppm of the raw material mixture.
[0025] In one possible implementation, the doping amount of the second metal ion is 500ppm-5000ppm of the raw material mixture.
[0026] Secondly, the present invention provides a lithium manganese iron phosphate cathode material obtained by the above preparation method.
[0027] Thirdly, the present invention provides a positive electrode sheet comprising the above-mentioned lithium manganese iron phosphate positive electrode material.
[0028] Fourthly, the present invention provides a secondary battery comprising the lithium manganese iron phosphate cathode material prepared by the above preparation method or the above cathode sheet.
[0029] The method for preparing lithium manganese iron phosphate cathode material provided by the present invention involves grinding and mixing a mixture of raw materials including phosphorus source, manganese source, iron source and lithium source with a first dopant containing a first metal ion with an ionic radius less than or equal to the manganese ion radius, followed by drying and sintering to obtain the cathode material. First, by leveraging the thermal decomposition temperature difference between the manganese and iron sources, manganese preferentially precipitates inside the droplets during the first spray drying process, while iron precipitates later on the droplet surface. This, combined with in-situ elemental distribution locking through instantaneous drying, creates a unique partitioned configuration with a low-manganese, iron-rich outer region and a high-manganese inner region, eliminating the need for secondary mixing. This significantly reduces the manganese concentration on the cathode material surface, weakening the disproportionation reaction and dissolution driving force of manganese in the electrolyte environment. This effectively prevents manganese dissolution from the cathode material surface, stabilizes the cathode material's crystal lattice interface, and allows the retention of a high-manganese component within the cathode material. This maintains the high voltage platform and high energy density advantages of lithium iron phosphate (LFP), ultimately significantly improving the room-temperature and high-temperature cycling performance of the LFP cathode material. Simultaneously, the incorporation of a first metal ion into the cathode material's inner region, without significantly disrupting the main crystal lattice, broadens the ion diffusion channels and lowers the migration barrier, significantly improving the lithium-ion conductivity and rate performance of the cathode material. The above preparation method effectively optimizes the composition and structure of lithium iron phosphate cathode material, thereby preparing lithium iron phosphate cathode material with both high rate transport characteristics and high cycle stability. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0031] In existing technologies, during cycling, the manganese element on the surface of lithium manganese iron phosphate cathode materials continuously dissolves due to Jahn-Teller distortion and electrolyte erosion, leading to the loss of active lithium, damage to the SEI film of the anode, and capacity decay. Traditional homogenization control strategies (such as bulk manganese reduction) can alleviate dissolution, but at the expense of the material's voltage and energy density; surface coating only provides physical isolation and cannot optimize the intrinsic structural differences of the material; single-element doping, because it does not distinguish between the needs of the surface and the core, results in insufficient performance synergy. Therefore, there is an urgent need for a technical solution that addresses the contradiction between manganese dissolution and kinetic performance at the root of the material structure.
[0032] Based on an in-depth analysis of the intrinsic defects of lithium manganese iron phosphate (LFP) materials, the inventors proposed a technical path for synergistic optimization from two dimensions: "regional element occurrence" and "differentiated doping." First, thermodynamic analysis revealed the difference in precipitation behavior between manganese salts (low-temperature decomposition) and iron salts (high-temperature decomposition) in the temperature field of spray-dried droplets. This characteristic was used to construct a gradient distribution structure with a high-manganese core and a low-manganese shell. Simultaneously, addressing the core's kinetic performance issues, doping with a first metal ion (kinetic optimization element) was proposed to broaden the lithium-ion diffusion channel and reduce the migration barrier. Finally, through a single preparation process, regional component division and differentiated doping were simultaneously achieved, forming a lithium manganese iron phosphate cathode material with both high cycle stability and high rate performance.
[0033] Based on this, the first aspect of the present invention provides a method for preparing lithium manganese iron phosphate cathode material, which includes the following steps:
[0034] A mixture of raw materials including phosphorus source, manganese source, iron source and lithium source and a first dopant are ground and mixed, and then spray-dried for the first time to obtain a first precursor powder; the first dopant includes a first metal ion, and the ionic radius of the first metal ion is less than or equal to the ionic radius of the manganese ion;
[0035] The first precursor powder was sintered in a protective atmosphere to obtain lithium manganese iron phosphate cathode material.
[0036] The raw material mixture is the basic raw material set used to construct the main lattice of lithium manganese iron phosphate, and the first dopant is a trace auxiliary component used to regulate ion migration behavior. Grinding ensures sufficient contact between the components at both the particle and droplet scales, reducing the risk of local segregation during subsequent heat treatment and providing a controllable basis for the spatial distribution differences of the components after spray drying. In this embodiment, the raw material mixture and the first dopant can be in the form of a slurry, suspension, wet mixture, or semi-dry mixture.
[0037] The particle size D50 of the phosphorus source is 1-5 μm, specifically a range of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any two of these.
[0038] The particle size D50 of the manganese source is 0.5-3μm, specifically a range of 0.5μm, 1μm, 2μm, 3μm or any two of these.
[0039] The particle size D50 of the iron source is 0.5-3μm, specifically a range of 0.5μm, 1μm, 2μm, 3μm or any two of these.
[0040] The lithium source has a particle size D50 of 2-10 μm, specifically a range of 2 μm, 4 μm, 6 μm, 8 μm, 10 μm or any two of these.
[0041] The particle size D50 of the first dopant is 0.1-1 μm, specifically a range of 0.1 μm, 0.5 μm, 1 μm, or any two of these.
[0042] The molar ratio of Li:(Mn+Fe):P in the raw material mixture is (1-2):(1-2):(1-2), specifically 1:1:1, 1:1:2, 1:2:1, 1:2:2, 2:1:1, 2:2:1 or 2:2:2.
[0043] The molar ratio of Mn to Fe is (1-9):(1-9), preferably 6:4.
[0044] The decomposition temperature of the manganese source is within the range of 150℃, 180℃, 200℃, 220℃, or any combination thereof; the decomposition temperature of the iron source is within the range of 240℃, 260℃, 280℃, 300℃, or any combination thereof. The temperature difference between the manganese and iron sources defines their different release or transformation behaviors during spray drying and subsequent heating stages, causing them to exhibit different migration, enrichment, and fixation sequences during precursor formation and thermal evolution. This contributes to the formation of a structural basis characterized by low manganese and high iron content in the outer region and high manganese and low iron content in the inner region.
[0045] Specifically, the phosphorus source can be ammonium dihydrogen phosphate, ammonium phosphate salts, or other compounds that can decompose and release phosphorus components.
[0046] Specifically, lithium sources can be lithium carbonate, lithium hydroxide, or lithium nitrate.
[0047] Specifically, manganese source can be manganese acetate tetrahydrate or manganese oxalate.
[0048] Specifically, the iron source can be ferrous oxalate dihydrate or ferric formate.
[0049] The first dopant may be a nitrate, acetate, or chloride containing a first metal ion.
[0050] Specifically, the first metal ion includes Mg 2+ Zn 2+ Ti 4+ V 3+ Mo 6+ W 6+ At least one of the following. Because the ionic radius of the first metal ion is no greater than that of the manganese ion, it can occupy part of the transition metal sites or adjacent sites in the crystal lattice, and participate in the structure building with a smaller lattice distortion, thereby reducing the structural stress of the high-manganese cathode system under high-voltage conditions and improving cycle stability.
[0051] The amount of the first metal ion introduced can be within the range of 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm or any two of these in the raw material mixture. The amount of the first metal ion incorporated is kept within the above low concentration range to ensure low content, uniform distribution and no significant damage to the main crystal lattice.
[0052] The inlet air temperature for the first spray drying is a range of 260℃, 280℃, 300℃ or any two of these, and the outlet air temperature is a range of 100℃, 110℃, 120℃ or any two of these.
[0053] The initial spray drying rate is a range of 5 mL / min, 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, or any combination thereof.
[0054] Specifically, spray drying is a granulation process in which liquid or semi-liquid materials are atomized into tiny droplets and rapidly desoluble and solidified in a hot air stream. Its function and role are to utilize the differences in thermal decomposition and solidification rates of different components to form a particle structure with preliminary partitioned component characteristics during droplet evaporation, thereby providing a stable precursor for the crystal phase transformation and elemental solidification in the subsequent sintering stage. The spray drying equipment for the first spray drying can adopt pressure spray, centrifugal spray, or airflow spray. The spray chamber can be combined with a hot air system, cyclone separator, and material collection device to form a continuous or intermittent drying unit. The first precursor powder is usually in the form of spherical, quasi-spherical, or core-shell particles, and a relatively gradient distribution of manganese, iron, phosphorus, lithium, and the first metal ions can be formed inside.
[0055] Specifically, the equipment used for grinding and mixing is a sand mill or a ball mill.
[0056] Specifically, the grinding and mixing speed is 500-700 r / min, and the ball milling time is 5-7 h.
[0057] In the first sintering process, the protective atmosphere is at least one of argon, helium, or nitrogen.
[0058] The sintering temperature for the first sintering is a range of 400℃, 500℃, 600℃, 700℃, 800℃ or any two of these, and the sintering time is a range of 1h, 5h, 10h, 15h, 20h, 24h or any two of these.
[0059] The first sintering stage is used to complete the olivine-type crystal phase transformation, carbonization residue regulation, and lattice solidification of doped elements under conditions that suppress oxidation side reactions. Its function and role are to form the target crystal structure of components such as lithium, manganese, iron, and phosphorus through high-temperature solid-phase diffusion, and to transform the partitioned distribution of the precursor stage into the final cathode material with a stable interface and better kinetic response. The first sintering stage is located at the end of the process, directly receiving the first precursor powder and outputting the finished lithium manganese iron phosphate cathode material. The first sintering device can be a box furnace, tube furnace, rotary kiln, or continuous sintering furnace. The sintering environment can be used with crucibles, boats, or refractory saggers. The final product is olivine-type lithium manganese iron phosphate crystal particles.
[0060] Based on the above analysis, the preparation method of lithium manganese iron phosphate cathode material provided by the present invention firstly involves grinding and mixing phosphorus source, manganese source, iron source, lithium source and first dopant to uniformly disperse each component under mechanical shearing and collision action and form a material system suitable for spraying; then, a first spray drying is performed under an inlet air temperature of 260-300℃ and an outlet air temperature of 100-120℃, so that the atomized droplets rapidly desoluble and solidify during heat exchange, thereby forming a first precursor powder with gradient or partitioned internal component distribution under the combined action of different raw material thermal decomposition behaviors; then, the first precursor powder is placed in a protective atmosphere for a first sintering, so that lithium, manganese, iron, phosphorus and the first dopant complete the construction and stabilization of olivine-type crystal phase under solid-phase diffusion conditions, and the spatial distribution characteristics in the precursor are solidified into the microstructure of the final material.
[0061] Due to the difference in thermal decomposition temperatures between manganese and iron sources, in the droplet temperature field of the first spray drying, manganese preferentially precipitates inside the droplet, while iron precipitates later on the droplet surface. In-situ elemental distribution is then locked in by instantaneous drying, creating a unique partitioned configuration with a low-manganese, iron-rich outer region and a high-manganese inner region without secondary mixing. This significantly reduces the manganese concentration on the cathode material surface, weakening the disproportionation reaction and dissolution driving force of manganese in the electrolyte environment. This effectively prevents manganese dissolution from the cathode material surface, stabilizes the cathode material's crystal lattice interface, and allows the retention of a high-manganese component within the cathode material to maintain the high-voltage platform and high-energy-density advantages of lithium iron phosphate (LFP). Ultimately, this significantly improves the room-temperature and high-temperature cycling performance of LFP cathode materials. Simultaneously, the incorporation of a first metal ion into the cathode material's inner region, without significantly disrupting the main crystal lattice, broadens the ion diffusion channels and lowers the migration barrier, significantly improving lithium-ion conductivity and rate performance. The above preparation method effectively optimizes the composition and structure of lithium iron phosphate cathode material, thereby preparing lithium iron phosphate cathode material with both high rate transport characteristics and cycle stability.
[0062] Further research by the inventors revealed that after the first sintering, the process also includes the following steps:
[0063] A second dopant is incorporated into the product of the first sintering, followed by a second spray drying to obtain a second precursor powder. The second dopant includes a second metal ion, the ionic radius of which is greater than that of the manganese ion.
[0064] The second precursor powder is then sintered a second time in a protective atmosphere to obtain lithium manganese iron phosphate cathode material.
[0065] The second dopant refers to a functional dopant containing a second metal ion, introduced after the first sintering, to further regulate the formed lithium manganese iron phosphate crystal phase. Its target is the particle system formed after the first sintering product is redispersed. The function of the second dopant is to differentiate the surface, near-surface, or grain boundary regions of the cathode material particles through the second metal ion (with an ionic radius larger than that of manganese ions). This makes it easier for the second metal ions to form an enriched or solid-solid state in the surface region of the cathode particles during the subsequent second spray drying granulation and second sintering process, thereby suppressing lattice distortion, interfacial reactions, and manganese dissolution, and improving structural stability during electrochemical cycling. Physically, the second dopant is usually introduced onto the surface of the powder of the first sintering product through mixing, impregnation, spraying, or dry remixing, and enters the second spray drying process together with the first sintering product. After the second spray drying, the second dopant and the main powder are redispersed to form a second precursor powder with a certain sphericity and particle size distribution, which is then used as input material for the second sintering in the protective atmosphere sintering stage.
[0066] In one possible embodiment, the second dopant may be a salt containing a second metal ion, such as a nitrate, acetate, oxalate, or chloride; in another possible embodiment, the second dopant may be an oxide, hydroxide, carbonate, or complex precursor containing a second metal ion.
[0067] Specifically, the second metal ion can be selected from Zr. 4+ 、Nb 5+ Ca 2+ Y 3+ Ce 3+ It can be at least one of the following, and can correspond to materials such as zirconium nitrate, niobium oxalate, calcium acetate, yttrium nitrate, and cerium nitrate.
[0068] The amount of the second metal ion added can be within the range of 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm or any two of these amounts from the raw material mixture.
[0069] After the product from the first sintering is fed into the remixing unit, the second dopant is added in a preset ratio and fully contacted with it, so that the second metal ions are preferentially adsorbed on the particle surface or enter the interparticle gaps. In the subsequent second spray drying process, the slurry containing the second dopant is atomized into droplets and rapidly desolvated, thereby obtaining a second precursor powder with a more uniform structure. After the second precursor powder enters the second sintering stage under a protective atmosphere, the second metal ions further migrate to the particle surface or near-surface region under the action of thermal diffusion, and form a stable modification layer or partial solid solution structure at the grain boundary, thereby synergistically optimizing the lithium ion transport channel and lattice stability.
[0070] Because the ionic radius of the second metal ion is larger than that of the manganese ion, it can form a more significant supporting and pinning effect in the local lattice, suppress Jahn-Teller distortion, reduce the accumulation of structural stress and the risk of manganese dissolution during cycling, and significantly reduce the amount of manganese dissolved. This fundamentally improves the lattice integrity and chemical stability of the material during long-term cycling, avoiding rapid capacity decay caused by the loss of active lithium. Therefore, introducing a second metal ion can further improve the cycling stability, interfacial stability, and overall kinetic performance of lithium manganese iron phosphate cathode materials, and the resulting cathode material exhibits superior structural retention capabilities in rate charge / discharge and long-term cycling applications.
[0071] The inlet air temperature of the second spray dryer is a range of 200℃, 250℃, 300℃, 350℃, 400℃ or any two of these, and the outlet air temperature is a range of 80℃, 100℃, 120℃, 150℃ or any two of these.
[0072] The feed rate of the second spray dryer is a range of 5 mL / min, 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, or any combination thereof.
[0073] The protective atmosphere for the second sintering is at least one of argon, helium, or nitrogen.
[0074] The sintering temperature of the second sintering is a range of 400℃, 500℃, 600℃, 700℃, 800℃ or any two of these, and the sintering time is a range of 1h, 5h, 10h, 15h, 20h, 24h or any two of these.
[0075] The equipment used for the second spray drying is the same as that used for the first spray drying, and the equipment used for the second sintering is the same as that used for the first sintering.
[0076] Based on further research by the inventors, it was found that before the first spray drying, a mixture of raw materials including phosphorus source, manganese source, iron source, lithium source, first dopant and carbon source are ground and mixed to obtain a reaction mixture, and the first spray drying is performed to obtain the first precursor powder.
[0077] The carbon source accounts for 10-14% of the mass of the reaction mixture.
[0078] The carbon source can be glucose, sucrose, or fructose.
[0079] By adding a carbon source, the carbon source decomposes at high temperature and forms a conductive carbon layer (carbon coating) on the particle surface, which builds an electron transport channel, reduces electrode polarization, and thus further improves the rate performance of lithium manganese iron phosphate cathode material.
[0080] A second aspect of the present invention provides a lithium manganese iron phosphate cathode material, which is obtained by the aforementioned preparation method.
[0081] By constructing a unique partitioned configuration within the cathode material particles—low-manganese, iron-rich outer regions and high-manganese inner regions—the manganese concentration on the cathode material surface is significantly reduced. This effectively prevents manganese leaching from the cathode material surface, stabilizes the cathode material's crystal lattice interface, and allows the high-manganese component to be retained within the cathode material's inner regions, maintaining the high-voltage platform and high-energy-density advantages of lithium iron phosphate. Simultaneously, the presence of the first metal ions within the cathode material's inner regions, without significantly disrupting the main crystal lattice, broadens the ion diffusion channels and lowers the migration barrier, significantly improving lithium-ion conductivity and rate performance. This cathode material maintains the high-rate transport characteristics of high-manganese cathode materials while enhancing its lattice integrity and chemical stability during long-cycle periods. This effectively prevents rapid capacity decay caused by manganese leaching leading to the loss of active lithium, significantly improving the battery's rate performance and cycle life.
[0082] A third aspect of the present invention provides a positive electrode sheet comprising the aforementioned lithium manganese iron phosphate positive electrode material.
[0083] Specifically, the positive electrode sheet is obtained by dry pressing or coating and drying the aforementioned lithium manganese iron phosphate positive electrode material on the positive electrode current collector.
[0084] By using the aforementioned lithium iron manganese phosphate cathode material and hot-pressing or coating it onto the cathode current collector to obtain a cathode sheet, the lithium iron manganese phosphate cathode material, through its special partitioned configuration of low manganese and iron-rich outer region and high manganese inner region, as well as the first metal ion doped in its inner region and the second metal ion doped in its surface region, can effectively prevent the dissolution of surface manganese and stabilize the lattice interface. This allows the high manganese composition to be retained in the inner region of the material, thus maintaining the high voltage platform and high energy density advantage of the lithium iron manganese phosphate cathode system. At the same time, it widens the ion diffusion channel, reduces the migration barrier, and significantly improves the lithium-ion conduction rate and rate performance of the cathode sheet.
[0085] Specifically, the positive electrode sheet includes a positive current collector and a positive active layer disposed on at least a portion of the surface of the positive current collector, the positive active layer including the aforementioned lithium manganese iron phosphate positive electrode material.
[0086] Specifically, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil.
[0087] Furthermore, in addition to lithium manganese iron phosphate cathode material, the cathode active layer also includes conductive agents and binders.
[0088] Specifically, the positive electrode active layer comprises, by weight percentage, 70-99 wt% lithium manganese iron phosphate positive electrode material, 0.5-15 wt% conductive agent, and 0.5-15 wt% binder.
[0089] Specifically, the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber.
[0090] Specifically, the adhesive may be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane.
[0091] A fourth aspect of the present invention provides a secondary battery comprising the aforementioned lithium manganese iron phosphate cathode material or the aforementioned cathode sheet.
[0092] Since the lithium manganese iron phosphate cathode material of the above-mentioned cathode sheet is the lithium manganese iron phosphate cathode material prepared in this invention, due to its special partitioned configuration of low manganese and rich iron in the outer region and high manganese in the inner region, as well as the first metal ion incorporated in the inner region, it can effectively prevent the dissolution of manganese on the surface, stabilize the lattice interface, and at the same time widen the ion diffusion channel and reduce the migration barrier, significantly improving the lithium ion conduction rate and rate performance, thereby improving the rate performance and cycle life of the battery.
[0093] In one possible implementation, the aforementioned lithium manganese iron phosphate cathode material is used to obtain a cathode sheet by dry pressing or coating and drying on a cathode current collector. After integrating the cathode sheet and the solid electrolyte layer, it is then assembled with a negative electrode sheet to obtain a secondary battery.
[0094] In another possible implementation, the secondary battery includes the aforementioned positive electrode, solid electrolyte layer and negative electrode, with the solid electrolyte layer stacked on the positive electrode and the negative electrode stacked on the side of the solid electrolyte layer away from the positive electrode.
[0095] Specifically, the solid electrolyte in the solid electrolyte layer includes at least one of garnet-type oxides, NASICON-type oxides, perovskite-type oxides, sulfide glass ceramics, and electrolyte halides.
[0096] Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer formed of negative electrode active material disposed on the surface of the negative electrode current collector.
[0097] Specifically, the material of the negative electrode current collector layer can be at least one of copper foil, nickel foam, and copper foam.
[0098] Specifically, the negative electrode active layer comprises, by weight percentage, 70-99 wt% negative electrode active material, 0.5-15 wt% conductive agent, and 0.5-15 wt% binder.
[0099] Specifically, the negative electrode active material can be selected from at least one of the following: mesophase carbon microspheres, natural graphite, artificial graphite, hard carbon, soft carbon, iron oxide, tin oxide, silicon oxide, silicon-carbon composites, lithium metal, and lithium metal alloys.
[0100] Specifically, the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.
[0101] Specifically, the adhesive may be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0102] In another possible implementation, the secondary battery includes the aforementioned positive and negative electrode plates, as well as an electrolyte and a separator.
[0103] This invention does not strictly limit the choice of electrolyte. The electrolyte may include one or more solvents commonly used in lithium-ion battery electrolytes, as well as lithium salts commonly used in lithium-ion electrolytes. Specifically, the solvent may be ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the lithium salt may be one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0104] Specifically, the diaphragm can be at least one of the following: polypropylene diaphragm (PP), polyethylene diaphragm (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polyimide electrospun diaphragm (PI), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), cellulose nonwoven fabric diaphragm, and diaphragm with ceramic coating.
[0105] The present invention will be further described below through specific embodiments.
[0106] Example 1:
[0107] The preparation method of the lithium iron manganese phosphate cathode material in the embodiment includes the following steps:
[0108] S1: Lithium carbonate, manganese oxalate, ferric formate, and ammonium dihydrogen phosphate were weighed as a raw material mixture according to the molar ratio of Li:(Mn+Fe):P=1:1:1 and the molar ratio of Mn:Fe=6:4; magnesium nitrate was weighed, wherein the amount of magnesium ions incorporated was 1000 ppm of the raw material mixture; finally, glucose was weighed, and the glucose was mixed with the above-mentioned raw material mixture and magnesium nitrate to obtain a reaction mixture, wherein the mass percentage of glucose was 12%.
[0109] S2: Add the above reaction mixture to deionized water and place it in a ball mill. Ball mill at 600 r / min for 6 h. After ball milling, perform a first spray drying. The inlet air temperature for the first spray drying is 280℃ and the outlet air temperature is 120℃ to obtain lithium manganese iron phosphate first precursor powder.
[0110] S3: The first precursor powder of lithium manganese iron phosphate is placed in a tube furnace, argon gas (Ar) is introduced, and it is calcined at 700°C for 10 hours to obtain the first sintered product.
[0111] S4: Zirconium nitrate is added to the product of the first sintering, wherein the amount of zirconium ions added is 1000 ppm of the raw material mixture. The product is then placed in a ball mill and ball-milled at 600 r / min for 6 h. After ball milling, a second spray drying is performed to obtain lithium manganese iron phosphate second precursor powder.
[0112] S5: The lithium manganese iron phosphate second precursor powder is placed in a tube furnace, argon gas (Ar) is introduced, and it is calcined at 700℃ for 10 hours to obtain the final lithium iron manganese iron phosphate cathode material.
[0113] Example 2:
[0114] The preparation method of the lithium iron manganese phosphate cathode material in this embodiment includes the following steps:
[0115] S1: Lithium carbonate, manganese oxalate, ferric formate, and ammonium dihydrogen phosphate were weighed as a raw material mixture according to the molar ratio of Li:(Mn+Fe):P=1:1:1 and the molar ratio of Mn:Fe=6:4; magnesium nitrate was weighed, wherein the amount of magnesium ions incorporated was 1000 ppm of the raw material mixture; finally, glucose was weighed, and the glucose was mixed with the above-mentioned raw material mixture and magnesium nitrate to obtain a reaction mixture, wherein the mass percentage of glucose was 12%.
[0116] S2: Add the above reaction mixture to deionized water and place it in a ball mill. Ball mill at 600 r / min for 6 h. After ball milling, perform a first spray drying. The inlet air temperature for the first spray drying is 280℃ and the outlet air temperature is 120℃ to obtain lithium manganese iron phosphate first precursor powder.
[0117] S3: The first precursor powder of lithium manganese iron phosphate is placed in a tube furnace, argon gas (Ar) is introduced, and it is calcined at 700°C for 10 hours to obtain lithium iron manganese iron phosphate cathode material.
[0118] Example 3:
[0119] The preparation method of lithium iron manganese phosphate cathode material in this embodiment differs from that in Example 1 in that the amount of magnesium ions incorporated is 500 ppm of the raw material mixture, and the amount of zirconium ions incorporated is 500 ppm of the raw material mixture.
[0120] Example 4:
[0121] The preparation method of lithium iron manganese phosphate cathode material in this embodiment differs from that in Example 1 in that the amount of magnesium ions incorporated is 5000 ppm of the raw material mixture, and the amount of zirconium ions incorporated is 5000 ppm of the raw material mixture.
[0122] Example 5:
[0123] The preparation method of lithium iron manganese phosphate cathode material in this embodiment differs from that in Example 1 in that the amount of magnesium ions incorporated is 400 ppm of the raw material mixture, and the amount of zirconium ions incorporated is 400 ppm of the raw material mixture.
[0124] Example 6:
[0125] The preparation method of lithium iron manganese phosphate cathode material in this embodiment differs from that in Example 1 in that the amount of magnesium ions incorporated is 5500 ppm of the raw material mixture, and the amount of zirconium ions incorporated is 5500 ppm of the raw material mixture.
[0126] Comparative Example 1:
[0127] The preparation method of the lithium iron manganese phosphate cathode material in this embodiment includes the following steps:
[0128] S1: Weigh lithium carbonate, manganese oxalate, ferric formate, and ammonium dihydrogen phosphate as raw material mixture according to the molar ratio of Li:(Mn+Fe):P=1:1:1 and the molar ratio of Mn:Fe=6:4; weigh glucose and mix the glucose with the above-mentioned raw material mixture to obtain a reaction mixture, wherein the mass percentage of glucose is 12%.
[0129] S2: Add the above reaction mixture to deionized water and place it in a ball mill. Ball mill at 600 r / min for 6 h. After ball milling, perform a first spray drying. The inlet air temperature for the first spray drying is 280℃ and the outlet air temperature is 120℃ to obtain lithium manganese iron phosphate first precursor powder.
[0130] S3: The first precursor powder of lithium manganese iron phosphate is placed in a tube furnace, argon gas (Ar) is introduced, and it is calcined at 700°C for 10 hours to obtain the first sintered product.
[0131] S4: Zirconium nitrate is added to the product of the first sintering, wherein the amount of zirconium ions added is 1000 ppm of the raw material mixture. The product is then placed in a ball mill and ball-milled at 600 r / min for 6 h. After ball milling, a second spray drying is performed to obtain lithium manganese iron phosphate second precursor powder.
[0132] S5: The lithium manganese iron phosphate second precursor powder is placed in a tube furnace, argon gas (Ar) is introduced, and it is calcined at 700℃ for 10 hours to obtain the final lithium iron manganese iron phosphate cathode material.
[0133] Comparative Example 2:
[0134] The preparation method of the lithium iron manganese phosphate cathode material in this embodiment includes the following steps:
[0135] S1: Weigh lithium carbonate, manganese oxalate, ferric formate, and ammonium dihydrogen phosphate as raw material mixture according to the molar ratio of Li:(Mn+Fe):P=1:1:1 and the molar ratio of Mn:Fe=6:4; weigh glucose and mix the glucose with the above-mentioned raw material mixture to obtain a reaction mixture, wherein the mass percentage of glucose is 12%.
[0136] S2: Add the above reaction mixture to deionized water and place it in a ball mill. Ball mill at 600 r / min for 6 h. After ball milling, perform a first spray drying. The inlet air temperature for the first spray drying is 280℃ and the outlet air temperature is 120℃ to obtain lithium manganese iron phosphate first precursor powder.
[0137] S3: The first precursor powder of lithium manganese iron phosphate is placed in a tube furnace, argon gas (Ar) is introduced, and it is calcined at 700°C for 10 hours to obtain lithium iron manganese iron phosphate cathode material.
[0138] Comparative Example 3:
[0139] The preparation method of lithium iron manganese phosphate cathode material in this embodiment differs from that in Example 1 in that manganese oxalate in the raw material mixture is replaced with manganese carbonate.
[0140] Experimental example:
[0141] 1) Resistivity test method: According to GB / T351-2019, the lithium iron manganese phosphate cathode materials of Examples 1-6 and Comparative Examples 1-3 were straightened, degreased and derusted, and placed in the same environment as the resistivity tester for 1 hour. At (20±5)℃, the dimensions of 5 points on the gauge length (≥300mm) were measured with a micrometer, and the average cross-sectional area was calculated. The resistance was measured using a Kelvin bridge (resistance <10Ω) or a Wheatstone bridge (resistance ≥10Ω), and the result was calculated according to the formula ρ=RA / L (ρ is resistivity, R is resistance, A is cross-sectional area, and L is gauge length). The total instrument error was ≤±0.15%, and the calculation results are shown in Table 1.
[0142] 2) Mn leaching test method: According to GB4806.9-2023 standard, the lithium iron manganese phosphate cathode materials of Examples 1-6 and Comparative Examples 1-3 were cut into 9mm×9mm samples, washed with deionized water, and then immersed in 3% acetic acid extraction solution at 40℃ for 24h. 5mL of the leachate was taken, microwave digested with concentrated nitric acid, cooled, and then diluted to 50mL with dilute nitric acid. The Mn leaching amount was calculated by comparing the parameters of an ICP instrument with the standard curve, using parameters set according to SN / T4513-2016. The results are shown in Table 1.
[0143] 3) Room temperature cycling performance test: Batteries were prepared using lithium iron manganese phosphate cathode materials from Examples 1-6 and Comparative Examples 1-3. The capacity retention rate of the batteries after 200 cycles was tested at 25°C. The specific conditions were: 25°C, 1C rate, voltage test window of 2.5-4.35V, and cutoff rate of 0.05C.
[0144] 4) High-temperature cycling performance test: Batteries were prepared using lithium iron manganese phosphate cathode materials from Examples 1-6 and Comparative Examples 1-3. The capacity retention rate of the batteries was tested after 200 cycles at 45°C. The specific conditions were: 45°C, 1C rate, voltage test window of 2.5-4.35V, and cutoff rate of 0.05C.
[0145] Table 1:
[0146]
[0147] First, in Example 1, manganese and iron sources with different thermal decomposition temperatures were used, and first and second metal ions were incorporated into the internal and external regions of the cathode material, respectively. As shown in Table 1, under high-voltage conditions, the resistivity and Mn dissolution of the lithium iron phosphate cathode material prepared in Example 1 were both low, and the corresponding battery exhibited high capacity retention rates at both room temperature and high temperatures.
[0148] Compared to Example 1, Comparative Example 1 did not incorporate the first metal ion into the cathode material. As shown in Table 1, the resistivity and Mn dissolution amount of Comparative Example 1 are significantly higher than those of Example 1, and the corresponding room temperature / high temperature capacity retention rates of the prepared batteries are significantly lower than those of Example 1.
[0149] Furthermore, compared to Example 1, Example 2 did not incorporate a second metal ion into the external region of the lithium manganese iron phosphate cathode material. As shown in Table 1, the resistivity and Mn dissolution amount of Example 2 are significantly higher than those of Example 1, and the corresponding room temperature / high temperature capacity retention rates of the prepared batteries are significantly lower than those of Example 1.
[0150] Furthermore, compared to Example 1, Comparative Example 2 did not incorporate the first metal ion into the internal region of the positive electrode material, nor did it incorporate the second metal ion into the external region of the positive electrode material. As shown in Table 1, the resistivity and Mn dissolution amount of Comparative Example 2 are much higher than those of Example 1, and the corresponding room temperature / high temperature capacity retention rates of the prepared batteries are much lower than those of Example 1.
[0151] As shown above, the present invention incorporates a first metal ion and a second metal ion into the internal and external regions of the lithium manganese iron phosphate cathode material, respectively. This significantly reduces the resistivity of the lithium manganese iron phosphate cathode material, effectively suppresses manganese dissolution, thereby effectively maintaining the high voltage platform and high energy density advantages of lithium iron phosphate, and greatly improving the cycle stability of the lithium manganese iron phosphate cathode material at room temperature and high temperature.
[0152] Compared to Example 1, the thermal decomposition temperature of the manganese source used in Comparative Example 3 is approximately 300°C, which is not significantly different from or only slightly different from the thermal decomposition temperature of the iron source. As shown in Table 1, the resistivity and Mn dissolution amount of Comparative Example 3 are much higher than those of Example 1, and the corresponding room temperature / high temperature capacity retention rates of the prepared batteries are much lower than those of Example 1. This indicates that the present invention, using manganese and iron sources with different thermal decomposition temperatures as raw materials, can result in higher electronic conductivity and a more stable crystal structure in the cathode material, maintaining a high capacity retention rate even under long-term cycling and high-temperature conditions. Furthermore, appropriate doping can improve the lattice stability of the material, thereby significantly improving the rate transport characteristics and room temperature / high temperature cycling stability of the lithium manganese iron phosphate cathode material.
[0153] Compared to Example 1, the doping amounts of the first and second metal ions in Example 3 are the lowest values within the scope defined by this invention, while the doping amounts of the first and second metal ions in Example 4 are the highest values within the scope defined by this invention. As shown in Table 1, the resistivity and Mn dissolution amounts of Examples 3-4 are slightly higher than those of Example 1, and the corresponding room temperature / high temperature capacity retention rates of the prepared batteries are slightly lower than those of Example 1. This indicates that the doping amounts of the first and second metal ions in Example 1 are relatively optimal.
[0154] Compared to Example 1, the doping amounts of the first and second metal ions in Examples 5-6 are all outside the range defined in this invention. As shown in Table 1, the resistivity and Mn dissolution amount of Examples 5-6 are significantly higher than those of Examples 1, 3, and 4, and the corresponding room temperature / high temperature capacity retention rates of the prepared batteries are slightly lower than those of Examples 1, 3, and 4. This indicates that the doping range of the first and second metal ions defined in this invention can significantly reduce the resistivity of lithium iron manganese phosphate cathode materials, effectively suppress manganese dissolution, thereby effectively maintaining the high voltage platform and high energy density advantages of lithium iron manganese phosphate, and improving the cycle stability of lithium iron manganese phosphate cathode materials at both room temperature and high temperature.
[0155] In summary, the preparation method of the present invention can synergistically optimize the conductivity, manganese leaching inhibition ability and long-term cycling stability of the material, and its overall performance is significantly better than conventional processes and comparative schemes.
[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a lithium manganese iron phosphate cathode material, characterized in that, Includes the following steps: A mixture of raw materials including phosphorus source, manganese source, iron source, and lithium source, and a first dopant are ground and mixed, and then subjected to a first spray drying to obtain a first precursor powder. The decomposition temperature of the manganese source is 150-220℃; the decomposition temperature of the iron source is 240-300℃; the manganese source is selected from manganese acetate tetrahydrate or manganese oxalate; the iron source is selected from ferrous oxalate dihydrate or ferric formate; the inlet air temperature of the first spray drying is 260-300℃, and the outlet air temperature is 100-120℃; the first dopant includes a first metal ion, which includes Mg. 2+ Zn 2+ Ti 4+ V 3+ Mo 6+ W 6+ At least one of the following, wherein the doping amount of the first metal ion is 500ppm-5000ppm of the raw material mixture; The first precursor powder was sintered for the first time in a protective atmosphere to obtain lithium manganese iron phosphate cathode material. After the first sintering is completed, the following steps are also included: A second dopant is incorporated into the product from the first sintering, followed by a second spray drying to obtain a second precursor powder; the second dopant comprises a second metal ion, which includes Zr. 4+ 、Nb 5+ Ca 2+ Y 3+ Ce 3+ At least one of them, wherein the doping amount of the second metal ion is 500ppm-5000ppm of the raw material mixture; The second precursor powder is then sintered a second time in a protective atmosphere to obtain lithium manganese iron phosphate cathode material.
2. The method for preparing lithium manganese iron phosphate cathode material according to claim 1, characterized in that: The protective atmosphere is at least one of argon, helium, or nitrogen; and / or, The initial spray drying rate is 5-50 mL / min; and / or, The sintering temperature for the first sintering is 400-800℃, and the sintering time is 1-24h.
3. The method for preparing lithium manganese iron phosphate cathode material according to claim 1, characterized in that: The inlet air temperature for the second spray drying is 200-400℃, and the outlet air temperature is 80-150℃; and / or, The infeed rate for the second spray drying is 5-50 mL / min; and / or, The second sintering temperature is 400-800℃, and the sintering time is 1-24h.
4. A lithium iron phosphate cathode material, characterized in that: Obtained by the preparation method according to any one of claims 1-3.
5. A positive electrode plate, characterized in that: Including the lithium manganese iron phosphate cathode material as described in claim 4.
6. A secondary battery, characterized in that: It includes the lithium manganese iron phosphate cathode material as described in claim 4 or the cathode sheet as described in claim 5.
Citation Information
Patent Citations
Lithium manganese iron phosphate positive electrode material, preparation method thereof and electrochemical device
CN119218963A
Lithium manganese iron phosphate positive electrode material and preparation method thereof
CN120914229A
